1986
DOI: 10.3758/bf03211491
|View full text |Cite
|
Sign up to set email alerts
|

Two extensions of the anchor-range effect

Abstract: A stimulus from one category increased the rated similarity oftwo stimuli from another category. In addition, "different" responses, but not "same" responses, to same-category stimuli became slower when they occurred in blocks of trials with a stimulus from a second category. Another experiment employed figural stimuli in which two small disks and a large or very large (extreme) disk were simultaneously present. The extreme disk led to slower "different" and faster "same" responses to the two small disks. Slow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1988
1988
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…26 As will become clear in Section 4.2, the difficulty is inherited by other theories that take up a similarly flat view of the application of causal knowledge in categorization. 27 It does not, however, serve as a direct argument against hybridism, pluralism, or eliminativism. 28 For recent discussions see (Casasanto and Lupyan [2015]; Machery [2015]).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…26 As will become clear in Section 4.2, the difficulty is inherited by other theories that take up a similarly flat view of the application of causal knowledge in categorization. 27 It does not, however, serve as a direct argument against hybridism, pluralism, or eliminativism. 28 For recent discussions see (Casasanto and Lupyan [2015]; Machery [2015]).…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that the similarity rating for two targets, even when confined to a single dimension, is influenced by the presentation of a third target that serves as a foil. For example, two small black disks, presented along with a large black disk, were judged to be more similar as the size of large disk increased (King and Atef-Vahid [1986]). This means that what one takes as the range of acceptable values for a dimension might change as one encounters new targets.…”
Section: The Range Desideratummentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, this principle holds across areas as diverse as the anchor-range effect (Gravetter & Lockhead, 1973;Pollack, 1952), the resolution of perceptual differences (Welch, 1978), and the aftereffect obtained by presenting one object and then a second similar object (Gibson, 1933). With figural stimuli, an extreme (anchor) object strengthens the gestalt established by two other objects and also increases the perceived similarity of the other objects (King & Atef-vahid, 1986;Lockhead, 1988). For example, in the research of Gaylord (1984) that Lockhead describes, a spatially extreme third dot made two other dots group and also made them appear closer together (i.e., in more similar spatial positions).…”
mentioning
confidence: 99%